Internet, Mobile Device, Social Media Use, and Gaming Behavior During COVID-19: A Systematic Review of Observational Studies - Kuppili, Pooja Patnaik; Shah, Bigya; Gyawali, Shreeya; Singh Balhara, Yatan Pal (Addicta: The Turkish Journal on Addictions, 2022)
This systematic review aimed to assess the pattern and factors associated with internet, mobile device, social media use, and gaming behavior during the COVID-19 pandemic. Increased internet, smartphone, social media use as well as online gaming were noted. Younger age group, anxiety, depressive symptoms, and stress were associated with an increase in internet, smartphone, and social media use. The majority of studies were of poor quality. These conclusions highlight the need to conduct research with robust methodology and implement public health initiatives which address those at greater risk to alleviate pathological use.
Keywords: COVID-19; gaming behavior; internet use; mobile device; social media use